Impact of exposure to intimate partner violence on CD4+ and CD8+ T cell decay in HIV infected women: longitudinal study. - Rachel Jewkes; Kristin Dunkle; Nwabisa Jama-Shai; Glenda Gray (PLoS ONE, 2015)
Intimate partner violence (IPV) is a risk factor for HIV acquisition in many settings, but little is known about its impact on cellular immunity especially in HIV infected women, and if any impact differs according to the form of IPV. We tested hypotheses that exposure to IPV, non-partner rape, hunger, pregnancy, depression and substance abuse predicted change in CD4+ and CD8+ T-cell count in a dataset of 103 HIV infected young women aged 15-26 enrolled in a cluster randomised controlled trial. Multiple regression models were fitted to measure rate of change in CD4 and CD8 and including terms for age, person years of CD4+/CD8+ T-cell observation, HIV positivity at baseline, and stratum. Exposure variables included drug use, emotional, physical or sexual IPV exposure, non-partner rape, pregnancy and food insecurity. Mean CD4+ T cell count at baseline (or first HIV+ test) was 567.6 (range 1121-114). Participants were followed for an average of 1.3 years. The magnitude of change in CD4 T-cells was significantly associated with having ever experienced emotional abuse from a current partner at baseline or first HIV+ test (Coeff -132.9 95% CI -196.4, -69.4 p<0.0001) and drug use (Coeff -129.9 95% CI -238.7, -21.2 p=0.02). It was not associated with other measures. The change in CD8 T-cells was associated with having ever experienced emotional abuse at baseline or prior to the first HIV+ test (Coeff -178.4 95%CI -330.2, -26.5 p=0.02). In young ART-naive HIV positive women gender-based violence exposure in the form of emotional abuse is associated with a faster rate of decline in markers of cellular immunity. This highlights the importance of attending to emotional abuse when studying the physiological impact of IPV experience and the mechanisms of its impact on women's health.